Coupling modulation for efficient wavelength conversion with the Stark-chirped rapid adiabatic passage - Ting Wan; Tengfei Wang; Wenhui Zhou; Changshui Chen (Results in Physics, 2020)
We investigate the influence of nonlinear crystal’s coupling modulation on wavelength conversion based on Stark-chirped rapid adiabatic passage. The result shows that the distribution of the efficient conversion is zonal with the change of coupling delay parameter. In addition, the efficient wavelength conversion can be performed in counterintuitive and intuitive order, which can reduce the restriction on the condition of conversion process compared to the stimulated Raman adiabatic passage. When the width parameter d12 is fixed, the larger the width parameter d22 is, the higher the maximum conversion efficiency is and the larger the bandwidth for efficient wavelength conversion is. These findings provide a theoretical basis for the efficient acquisition of laser sources from the visible to the mid-infrared and to the ultraviolet.